Muscle Cell and Tissue - Current Status of Research Field 2018
DOI: 10.5772/intechopen.77108
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cells (VSMCs) in Blood Vessel Tissue Engineering: The Use of Differentiated Cells or Stem Cells as VSMC Precursors

Abstract: Vascular smooth muscle cells (VSMCs) play important roles in the physiology and pathophysiology of the blood vessels. In a healthy adult organism, VSMCs are quiescent, but after a blood vessel injury, they undergo phenotypic modulation from the contractile phenotype to the synthetic phenotype, characterized by high activity in migration, proliferation and proteosynthesis. This behavior of VSMCs can lead to stenosis or obliteration of the vascular lumen. For this reason, VSMCs have tended to be avoided in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…This was proven by the expression of an SMC marker calponin. Greater cell population density and greater upregulation of early differentiation markers α-actin and calponin were achieved in a pressure-stimulated culture than in static conditions [18,32]. In this context, two mechanosensitive signaling pathways associated with SMC differentiation have been described: the RhoA-associated pathway, and the FAK kinase-associated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This was proven by the expression of an SMC marker calponin. Greater cell population density and greater upregulation of early differentiation markers α-actin and calponin were achieved in a pressure-stimulated culture than in static conditions [18,32]. In this context, two mechanosensitive signaling pathways associated with SMC differentiation have been described: the RhoA-associated pathway, and the FAK kinase-associated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, harvesting of mature SMCs from the walls of large vessels presents a clinical challenge, 79 and fibroblasts may not produce vessels of the same quality as other support cell types. 77 The use of MSCs is therefore of particular interest in tissue engineering, since these cells are abundantly available, secrete proangiogenic factors, 11,80,81 and have the ability to differentiate toward an SMC lineage.…”
Section: Coupled Osteogenesis and Vasculogenesis 203mentioning
confidence: 99%
“…They are abundant in the mid-membrane of biological vascular tissues and are responsible for producing ECM while maintaining vascular mechanical properties. 8,11,12 VSMCs exhibit great plasticity and are not terminally differentiated cells. 13 It has been demonstrated that VSMCs can change from a stable contractile phenotype to a proliferative synthetic phenotype under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The two phenotypes of VSMCs exhibit different characteristics, with synthetic VSMCs found to have higher proliferative activity and migration ability, as well as the ability to promote the deposition of ECM. 11,12,14 The three-dimensional culture environment has a complex effect on the cellular behavior of seeded cells during the culture process, with a variety of effects having been reported. 15,16 Tumor necrosis factor-alpha (TNF-α) is an inflammatory cytokine with complex and potentially contradictory impacts on cardiac function and pathology, including beneficial effects.…”
Section: Introductionmentioning
confidence: 99%